Forest Area from ERTS-I MSS False Colour Composites - Tiwari, K. P. (Indian Forester, 1975)
False colour composites (band 4,5,7) from ERTS-I MSS data were interpreted by conventional methods for forestry purposes of an area falling between 28 ° 30' to 30 °30' N latitude and 77 ° 30' to 80 °00' E longitude. Topography, drainage pattern, waterbodies, forest and non-forest areas could be separated out by colour differences. Three different shades in red colour namely dark red, brownish red and pink accounted respectively for Sal forest, Conifers and Eucalyptus and other broadleaved vegetation. Forest area was compared with one million scale topographical maps obtained by reduction of 1:250,000 maps. No significant difference was found. Usefulness of ERTS-I MSS imageries for resource evaluation along with future scope and suggestions have been highlighted.